2004
DOI: 10.1074/jbc.m400781200
|View full text |Cite
|
Sign up to set email alerts
|

Function of Drg1/Rit42 in p53-dependent Mitotic Spindle Checkpoint

Abstract: Mutations in the Drg1/RTP/Rit42 gene are commonly identified in hereditary neuropathies of the motor and sensory systems. This gene was also identified as a p53 target gene and a differentiation-related, putative metastatic suppressor gene in human colon and prostate cancer. In this study, we show that the Rit42 protein is a microtubule-associated protein that localizes to the centrosomes and participates in the spindle checkpoint in a p53-dependent manner. When ectopically expressed and exposed to spindle inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 25 publications
4
51
0
1
Order By: Relevance
“…These data confirm our results in MCF10A cells and demonstrate that the level of NDRG1 directly regulates centrosome homeostasis. A potential interaction between NDRG1 and γ-tubulin has been previously reported as both proteins are present within the same fraction in cosedimentation assays (22). To confirm that NDRG1 directly interacts with centrosome assembly and mitotic division in vitro, a proximity ligation assay (PLA) was carried out with antibodies against NDRG1 and γ-tubulin.…”
Section: Homozygous Deletion Of Tp53 Is Mutually Exclusive With Ndrg1mentioning
confidence: 89%
See 1 more Smart Citation
“…These data confirm our results in MCF10A cells and demonstrate that the level of NDRG1 directly regulates centrosome homeostasis. A potential interaction between NDRG1 and γ-tubulin has been previously reported as both proteins are present within the same fraction in cosedimentation assays (22). To confirm that NDRG1 directly interacts with centrosome assembly and mitotic division in vitro, a proximity ligation assay (PLA) was carried out with antibodies against NDRG1 and γ-tubulin.…”
Section: Homozygous Deletion Of Tp53 Is Mutually Exclusive With Ndrg1mentioning
confidence: 89%
“…NDRG1 encodes the 46-kDa protein, NDRG1, which is highly conserved among multicellular organisms and is ubiquitously expressed in tissues in response to cellular stress (20). Prior studies demonstrated that NDRG1 is necessary but not sufficient for p53-mediated apoptosis (21) and may play a role in spindle organization, as NDRG1 has been shown to colocalize with centrosomes (22). However, NDRG1 as a direct mediator of p53-regulated centrosome homeostasis has not been demonstrated.…”
Section: Distinct Phenotypes Of P53 Null Versus P53 R248w Heterozygousmentioning
confidence: 99%
“…Recent reports that overexpression or knockdown of NDRG1 in cultured neoplastic cells alters their proliferation, differentiation, metastasis, and apoptosis statuses (25,28,29,(55)(56)(57)(58) and that genetic mutations in the Ndrg1 gene cause Schwann cell dysfunction leading to peripheral neuropathy in both human and mouse (30 -32) imply that this inducible intracellular protein plays roles in diverse processes linked to these cellular events. Despite its widespread distribution, however, the regulatory expression and functions of NDRG1, particularly in the immune system, have been poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Rit42 seems to play a role in the regulation of microtubule dynamics and the maintenance of euploidy (58). Rit42 is known to be down-regulated during colon and prostate tumor progression (59,60).…”
Section: Microtubule Motor Proteins and Spindle Checkpoint Componentsmentioning
confidence: 99%